Amidoxime-modified and titanium-doped MOFs (Metal-Organic Frameworks) material as well as preparation method and application thereof
Ti-MIL-101 and AO-Ti-MIL-101 materials were prepared through titanium doping and amidoxime group modification methods, which solved the shortcomings of existing MOFs materials in terms of uranium adsorption performance and stability in water, and achieved Efficient adsorption effect under low and high concentration conditions.
Patent Information
- Application Number
- CN202411444597.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-21
AI Technical Summary
The existing MOFs materials have shortcomings in the adsorption performance and stability of uranium in water, especially in poor results under high concentration conditions.
By synthesizing Ti-MIL-101 and AO-Ti-MIL-101 materials, titanium doping and amidoxime-based modification technologies are used to optimize the structural properties of the materials, and through solvothermal method, displacement reaction and graft modification, etc. Steps to Preparation.
The specific surface area and pore volume of the material are significantly increased, and the adsorption capacity and stability of uranyl ions are enhanced, especially under low and high concentration conditions, showing efficient adsorption performance.
Smart Images

Figure CN119331259A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal framework materials, and in particular to an amidoxime-modified and titanium-doped MOFs material, a preparation method thereof, and an application thereof. Background Art
[0002] As a new type of material, MOFs has been widely used in many fields since its development. MIL-101(Cr), as a branch of the MIL series of MOFs materials, has many advantages such as large specific surface area and high water stability. Its adsorption performance is far superior to traditional inorganic adsorption materials, and it has attracted much attention in the field of adsorption materials.
[0003] MIL-101, a classic representative of the MILs series, has the characteristics of high specific surface area, strong stability, and porosity. It has many applications in the fields of photocatalysis, medicine, material separation and storage, and is also a commonly used framework for preparing new uranium adsorption materials in water. MIL-101 (Cr) itself has a large number of unsaturated metal nodes, which can be chelated with the lone electron pairs on the N atom by post-modification, which provides the possibility of introducing AO functional groups. The introduction of AO groups can enhance the adsorption properties of the material, thereby improving the adsorption properties of the material. The amidoxime functional group (RN = O) is the most promising functional group in the field of uranium adsorption in water. It consists of an oxime group and an amine group, in which the nitrogen atom forms a single bond with the carbon atom and a double bond with the oxygen atom, which makes it have high affinity for uranyl ions, fast adsorption rate, good selectivity and other excellent characteristics, and has a wide range of applications in the field of uranium adsorption in water.
[0004] At the same time, metal ion doping can optimize the structural properties of materials, for example, Ti 4+ Doping can enhance the stability of the molecular structure of MOFs materials. On the one hand, Ti 4+ It can enhance the ionic bonding between the metal ion center and the organic framework structure; on the other hand, Ti 4+ / Ti 3+ The mutual transformation can be achieved within the lattice, which is beneficial to the electron transfer within the crystal. It can flexibly adjust the dynamic balance of the material's adsorption and desorption of oxygen atoms in uranyl ions, thereby enhancing the adsorption performance and stability of MOFs materials for uranium in water. Summary of the invention
[0005] In order to comprehensively solve the above problems, the present invention synthesizes Ti-MIL-101 and AO-Ti-MIL-101 materials, and then characterizes the materials. By analyzing the microscopic morphology characteristics of the materials, the correctness of the material preparation method is determined, and further the adsorption mechanism of the two materials on uranyl ions is explored through uranium adsorption experiments in water, the effects of parameters such as solution adsorption temperature and initial uranyl ion concentration on the adsorption performance of the materials are explored, and the adsorption mechanism of the materials is explored through thermodynamic analysis.
[0006] In order to achieve the above-mentioned object, the first aspect of the present invention provides an amidoxime-modified and titanium-doped MOFs material, which consists of AO-Ti-MIL-101.
[0007] The second aspect of the present invention provides a method for preparing an amidoxime-modified and titanium-doped MOFs material, comprising:
[0008] Step 1: Using terephthalic acid and chromium nitrate nonahydrate as raw materials, MIL-101(Cr) was synthesized by a solvothermal method;
[0009] Step 2: Using MIL-101(Cr) and butyl titanate as raw materials, shaking and mixing, and then performing a replacement reaction to obtain a Ti-doped MIL-101 material;
[0010] Step 3: Using Ti-doped MIL-101 material and aminoacetonitrile as raw materials, prepare aminoacetonitrile functionalized Ti-MIL-101 material; prepare hydroxylamine hydrochloride solution, dissolve the aminoacetonitrile functionalized Ti-MIL-101 material in the hydroxylamine hydrochloride solution, and obtain AO-Ti-MIL-101 after centrifugation and drying.
[0011] Preferably, step 1 comprises:
[0012] Step 1.1: Weigh terephthalic acid and dissolve it in water, stir it with electromagnetic stirring to dissolve, and obtain a white suspension;
[0013] Step 1.2: Weigh chromium nitrate nonahydrate and dissolve it in ultrapure water, and sequentially treat it with electromagnetic stirring and ultrasonic vibration to obtain a dark green solution;
[0014] Step 1.3: The two liquids obtained in step 1.1 and step 1.2 are mixed, stirred thoroughly and transferred to a high-pressure reactor, and the high-pressure reactor is placed in a forced air drying oven for reaction to obtain a green suspension containing MIL-101 (Cr).
[0015] Step 1.4: Place the green suspension in step 1.3 in a centrifuge to obtain a green solid precipitate;
[0016] Step 1.5: The green solid precipitate is washed with DMF, anhydrous ethanol and ultrapure water for 8 hours in sequence to remove impurities in the pores; and after centrifugation, suction filtration, vacuum drying and grinding, a green powdery MIL-101 (Cr) material is obtained.
[0017] Preferably, step 2 comprises:
[0018] Step 2.1: Disperse butyl titanate in anhydrous ethanol, then add MIL-101(Cr) and fully dissolve it;
[0019] Step 2.2: Place the mixed solution of step 2.1 in an oscillator for treatment;
[0020] Step 2.3: The mixed solution after the shaking treatment is placed in a vacuum drying oven for replacement reaction, and finally separated and dried to obtain the metal ion Ti-doped MIL-101 material.
[0021] Preferably, step 3 comprises:
[0022] Step 3.1: Disperse the Ti-MIL-101 material in anhydrous toluene, add aminoacetonitrile, condense and reflux under magnetic stirring, and then wash out the aminoacetonitrile functionalized Ti-MIL-101 material, i.e., AA-Ti-MIL-101, with anhydrous ethanol;
[0023] Step 3.2: dissolving methanol in deionized water, and then dissolving hydroxylamine hydrochloride in the methanol solution;
[0024] Step 3.3: dissolving the AA-MIL-101 prepared in step 3.1 in the solution prepared in step 3.2, adjusting the pH value of the solution to 7, stirring, and centrifuging;
[0025] Step 3.3: The sample obtained by centrifugation in step 3.3 is placed in a vacuum drying oven for drying, and finally amidoxime functionalized MIL-101 material, namely AO-Ti-MIL-101, is obtained.
[0026] Preferably, in step 1.3, the high-pressure reactor is placed in a forced air drying oven and reacted at 180° C. for 480 min.
[0027] Preferably, in step 2.1, the mass ratio of butyl titanate to anhydrous ethanol is 1:2; the mass ratio of MIL-101(Cr) to butyl titanate is 1:2.
[0028] Preferably, in step 3.1, the mass ratio of MIL-101(Cr) to aminoacetonitrile is 1:60; and the volume ratio of anhydrous toluene to the mass ratio of MIL-101(Cr) is 60 mL:1 g.
[0029] The third aspect of the present invention provides an amidoxime-modified and titanium-doped MOFs material prepared by the above method, which is used for preparing a uranium adsorbent.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] (1) The specific surface area of Ti-MIL-101 material is 1171.5 m 2 ·g -1 , pore diameter 0.5793nm, average pore volume 1.978cm 3 ·g -1 ; The specific surface area of AO-Ti-MIL-101 material is increased to 1511.6m 2 ·g -1 The increase in specific surface area is due to AO grafting modification, which can provide more adsorption active sites, and its average pore volume is 2.018cm 3 ·g -1 , the pore diameter is 2.62nm.
[0032] (2) Doping the material with metal ions Ti can enhance the material's adsorption capacity for uranyl ions. -1 ) the removal rate of uranyl ions by Ti-MIL-101 material can reach 93.78% at 20℃ and high concentration (100mg·L -1 ) under the condition of Ti-MIL-101, the removal rate of uranyl ions by Ti-MIL-101 material was 82.51%.
[0033] (3) On the basis of metal ion Ti doping, further AO grafting modification can further improve the adsorption performance of the material. -1 ) condition, the adsorption efficiency of uranyl ions by AO-Ti-MIL-101 material was as high as 97.72%; and at high concentration (100 mg·L -1 ) environment, the removal rate of uranyl ions by this material is 87.85%.
[0034] (4) The adsorption process of Ti-MIL-101 and AO-Ti-MIL-101 is characterized by bonding chemical adsorption. Through thermodynamic analysis, in the range of 20℃~40℃, increasing the temperature is beneficial to improving the adsorption performance of the material. The adsorption process of Ti-MIL-101 and AO-Ti-MIL-101 is more consistent with the Langmiur isotherm adsorption model, but there are monolayer adsorption and non-uniform surface adsorption processes at the same time. Among them, the adsorption capacity of Ti-MIL-101 can reach 150.62mg·g -1 The theoretical maximum adsorption capacity is 326.51 mg·L -1; The adsorption capacity of AO-Ti-MIL-101 can reach 185.35 mg·g -1 The theoretical maximum adsorption capacity is 404.67 mg·L -1 .
[0035] (5) Through SEM, XRD, and FTIR characterization and analysis, the morphology and phase composition of the two materials did not change significantly before and after adsorption, indicating that the materials have good stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The accompanying drawings are used to provide further understanding of the present invention and constitute a part of the specification. They are used to explain the present invention together with the embodiments of the present invention and do not constitute a limitation of the present invention.
[0037] In the attached picture:
[0038] Figure 1 This is the SEM image of Ti-MIL-101 of the present invention;
[0039] Figure 2 This is the SEM image of AO-Ti-MIL-101 of the present invention;
[0040] Figure 3 XRD diagram of the material prepared for the present invention;
[0041] Figure 4 In the figure, (a) nitrogen isothermal adsorption-desorption curve of Ti-MIL-10; (b) nitrogen isothermal adsorption-desorption curve of AO-Ti-MIL-101;
[0042] Figure 5 FTIR images of Ti-MIL-101 and AO-Ti-MIL-101 of the present invention;
[0043] Figure 6 The removal effect of Ti-MIL-101 and AO-Ti-MIL-101 of the present invention;
[0044] Figure 7 is the adsorption amount of uranyl ions by Ti-MIL-101 and AO-Ti-MIL-101 of the present invention;
[0045] Figure 8 The graph of the variation of uranium adsorption amount of Ti-MIL-101 with initial concentration under different temperature conditions of the present invention;
[0046] Fig. 9 It is the Langmiur model fitting diagram of Ti-MIL-101 material of the present invention;
[0047] Fig.10 The Freundlich model fitting of the Ti-MIL-101 material of the present invention;
[0048] Fig.11 This is a graph showing the variation of the adsorption capacity of AO-Ti-MIL-101 with the concentration of uranyl solution under different temperature conditions of the present invention;
[0049] Fig.12 It is the Langmiur model fitting diagram of AO-Ti-MIL-101 material of the present invention;
[0050] Fig.13 It is the Freundlich model fitting diagram of the AO-Ti-MIL-101 material of the present invention;
[0051] Fig.14 XRD comparison diagram of different materials before and after adsorption in the present invention;
[0052] Fig.15 In the figure, (a) SEM image of Ti-MIL-101 before adsorption, (b) SEM image of Ti-MIL-101 after adsorption, (c) SEM image of AO-Ti-MIL-101 material before adsorption, (d) SEM image of AO-Ti-MIL-101 material after adsorption;
[0053] Fig.16 FTIR images of the AO-Ti-MIL-101 material of the present invention before and after adsorption;
[0054] Fig.17 It is a flow chart of the preparation method of the present invention. DETAILED DESCRIPTION
[0055] The following combination Figure 1-Figure 17 It should be understood that the preferred embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0056] Table 1 Chemical specifications of the present invention
[0057]
[0058] Embodiment 1:
[0059] The invention discloses an amidoxime-modified and titanium-doped MOFs material, which has the composition of AO-Ti-MIL-101.
[0060] Embodiment 2:
[0061] A method for preparing amidoxime-modified and titanium-doped MOFs material, comprising:
[0062] Step 1: Using terephthalic acid and chromium nitrate nonahydrate as raw materials, MIL-101(Cr) is synthesized by a solvothermal method; comprising:
[0063] Step 1.1: Weigh 2.0 g of terephthalic acid (C8H6O4) and dissolve it in 40 mL of 70°C water, stir it with electromagnetic stirring to dissolve, and obtain a white suspension;
[0064] Step 1.2: Weigh 4.81 g of chromium nitrate nonahydrate (Cr(NO3)3·9H2O) and dissolve it in 20 mL of ultrapure water, and treat it with electromagnetic stirring and ultrasonic vibration for 20 min in sequence to obtain a dark green solution;
[0065] Step 1.3: The two liquids obtained in step 1.1 and step 1.2 are mixed, stirred thoroughly and transferred to a high-pressure reactor, which is placed in a forced air drying oven and reacted at 180° C. for 480 min to obtain a green suspension containing MIL-101 (Cr).
[0066] Step 1.4: Place the green suspension from step 1.3 in a centrifuge at 3000 r / min. -1 Centrifuge for 10 min to obtain a green solid precipitate;
[0067] Step 1.5: The green solid precipitate was washed with 50 mL DMF, anhydrous ethanol and ultrapure water for 8 h to remove impurities in the pores; and then centrifuged, filtered and vacuum dried at 60 ° C for 12 h, and ground to obtain a green powdery MIL-101 (Cr) material.
[0068] Step 2: Using MIL-101 (Cr) and butyl titanate as raw materials, shaking and mixing, and then performing a replacement reaction to obtain a Ti-doped MIL-101 material; comprising:
[0069] Step 2.1: Disperse butyl titanate in anhydrous ethanol, then add MIL-101(Cr) and fully dissolve; the mass ratio of butyl titanate to anhydrous ethanol is 1:2; the mass ratio of MIL-101(Cr) to butyl titanate is 1:2;
[0070] Step 2.2: Place the mixed solution of step 2.1 into an oscillator and process at a frequency of 130 Hz for 30 minutes;
[0071] Step 2.3: The mixed solution after the shaking treatment is placed in a vacuum drying oven, and the replacement reaction is carried out at a temperature of 70° C. for 12 hours. Finally, the metal ion Ti-doped MIL-101 material is obtained by separation and drying.
[0072] Step 3: Using Ti-doped MIL-101 material and aminoacetonitrile as raw materials, prepare aminoacetonitrile functionalized Ti-MIL-101 material; prepare hydroxylamine hydrochloride solution, dissolve the aminoacetonitrile functionalized Ti-MIL-101 material in the hydroxylamine hydrochloride solution, centrifuge and dry to obtain amidoxime functionalized MIL-101 material, i.e., AO-Ti-MIL-101. Including:
[0073] Step 3.1: Disperse the Ti-MIL-101 material in anhydrous toluene, add aminoacetonitrile, condense and reflux at 110°C under magnetic stirring for 12 hours, and then wash out the aminoacetonitrile-functionalized Ti-MIL-101 material, i.e., AA-Ti-MIL-101, with anhydrous ethanol; the mass ratio of MIL-101 (Cr) to aminoacetonitrile is 1:60; the volume (mL) of anhydrous toluene is to the mass (g) of MIL-101 (Cr) is 60:1.
[0074] Step 3.2: Dissolve 40 mL of methanol in 60 mL of deionized water, and then dissolve 1.1 g of hydroxylamine hydrochloride in the methanol solution;
[0075] Step 3.3: dissolving the AA-MIL-101 prepared in step 3.1 in the methanol solution prepared in step 3.2, adjusting the pH value of the solution to 7, stirring at 70°C for 12 hours, and centrifuging;
[0076] Step 3.3: The sample obtained by centrifugation in step 3.3 was placed in a vacuum drying oven and dried at 70° C. for 12 h to finally obtain the amidoxime functionalized MIL-101 material, namely AO-Ti-MIL-101.
[0077] Embodiment 3:
[0078] For example, an amidoxime-modified and titanium-doped MOFs material as described in Example 1 is used to prepare a uranium adsorbent.
[0079] test:
[0080] 1.1 Characterization of physical and chemical properties
[0081] (1) SEM / EDS characterization
[0082] Depend on Figure 1 It can be seen that after the metal ion titanium doping of MIL-101(Cr), the material still maintains its regular octahedral structure, and the titanium ions are adsorbed on the surface of MIL-101(Cr), making the surface of the material irregular, which may be due to the hydrolysis of butyl titanate and the deposition of nanoparticles on the surface. However, the use of this method to dope titanium ions will also make the agglomeration of the material more serious.
[0083] Depend on Figure 2It can be seen that after the introduction of amidoxime functional groups on Ti-MIL-101, the original octahedral structure becomes clear and the material agglomeration phenomenon weakens. This is because the introduction of AO increases the electronegativity of the material by the lone pair electrons on the N and O atoms, effectively preventing the agglomeration between crystal molecules; however, after doping with Ti, the surface of the AO-Ti-MIL-101 material becomes irregular, which may be due to the nanoparticles deposited on the surface by the hydrolysis of butyl titanate.
[0084] (2) XRD characterization
[0085] XRD was used to characterize the crystal structure of the material. Figure 3 As shown in the figure, compared with the published MIL-101 literature, the XRD spectrum has sharp peaks and obvious characteristic peaks, which are consistent with the literature. This proves that the MIL-101 crystal material was successfully prepared in this experiment. At the same time, after Ti doping of MIL-101, obvious diffraction peaks appeared between 25 and 30°. This may be that butyl titanate was hydrolyzed to generate titanium dioxide nanoparticles (deposited on the surface of the regular octahedron). After AO grafting modification, the diffraction peak of titanium dioxide disappeared. This is because the N and O lone pairs of electrons in the AO group enhance the electronegativity of the material, promote the doping of Ti into the lattice of MIL-101, and reduce the hydrolysis effect of butyl titanate, which is also the key to enhancing the adsorption performance.
[0086] (3) BET characterization
[0087] Nitrogen isothermal adsorption-desorption curves of Ti-MIL-101 and AO-Ti-MIL-101 are shown in Figure 4 (a). It can be seen that the two materials are mainly microporous materials, but AO-Ti-MIL-101 has a weak hysteresis loop during the desorption process ( Figure 4 a), indicating that there are still trace mesoporous structure adsorption characteristics; Figure 4 As shown in (b), the pore size distribution shows that after AO modification, the pore volume of AO-Ti-MIL-101 material is greatly increased, concentrated in the mesopore range with a diameter of 2nm to 2.5nm. In addition, the specific surface area of Ti-MIL-101 after AO grafting modification increased from 1171.5m 2 ·g -1 Increased to 1511.6m 2 ·g -1 , indicating that the AO-Ti-MIL-101 material has more adsorption active sites, as shown in Table 2.
[0088] Table 2 BET analysis of Ti-MIL-101 and AO-Ti-MIL-101
[0089]
[0090] (4) FTIR characterization
[0091] FTIR characterization of Ti-MIL-101 and AO-Ti-MIL-101 Figure 5 As shown, at 1539cm -1 The presence of a characteristic peak due to the stretching vibration of C=N in the amidoxime group indicates that AO grafting is successful. -1 The high intensity absorption peak of MIL-101(Cr) is caused by the OC=O symmetry, but the absorption peak at 1622cm -1 The absorption peak at 3354cm is caused by the asymmetric stretching vibration of the organic ligand diformate. -1 、754cm -1 、584cm -1 The wide peak at the top is mainly caused by crystal water. After grafting AO, the crystal water peak intensity of AO-Ti-MIL-101 material is significantly reduced, which is because the introduction of AO reduces the hydrogen bonding between water molecules and the organic framework.
[0092] 1.2 Test of uranium adsorption performance in water
[0093] (1) Low concentration adsorption performance test
[0094] Depend on Figure 6 It can be seen that when the Ti-MIL-101 material reaches adsorption equilibrium, its removal efficiency of uranyl ions reaches 93.78%; and when AO-Ti-MIL-101 reaches adsorption equilibrium, its removal efficiency of uranyl ions is increased to 97.72%. The average adsorption rate of Ti-MIL-101 and AO-Ti-MIL-101 in the first 0.5h is greater than that of MIL-101(Cr), and most of the adsorption work has been completed within 0.5h, and the adsorption rate has gradually slowed down after 0.5h. The adsorption rate of uranyl ions of these two materials is significantly greater than that of MIL-101(Cr) adsorption material, which indicates that after the modification of MIL-101(Cr), the removal rate of uranium in water at low concentrations has been improved to a certain extent.
[0095] (2) High concentration adsorption performance test
[0096] Depend on Figure 7It can be seen that in the high-concentration uranyl ion attachment test with time as a variable, the increase in the uranyl ion removal rate generally shows a decreasing trend over time. It is calculated that the removal rate of Ti-MIL-101 material is 82.51% at 4h, which is higher than the 80.24% adsorption removal rate of MIL-101(Cr) material for uranyl ions; the removal rate of AO-Ti-MIL-101 material is 87.85%, which is significantly higher than that of MIL-101(Cr) and Ti-MIL-101. This shows that after the modification of MIL-101(Cr), the material has a certain improvement in the removal rate of uranium in water at high concentrations.
[0097] 1.3 Thermodynamic analysis of uranium adsorption in water
[0098] In three different temperature environments, experimental data on the initial concentration of uranyl ions and the amount of material adsorption were obtained, such as Figure 8 As shown in the figure, when the initial concentration increases, the adsorption capacity of the material also increases, showing an overall trend of first fast and then slow, and finally reaching saturation. Under normal temperature conditions (20°C), the maximum adsorption capacity of Ti-MIL-101 material is 241.15 mg·g -1 .
[0099] The Langmiur model and Freundlich model were used to perform linear simulation on the adsorption data of Ti-MIL-101. The results are shown in Fig. 9 , Fig.10 As shown in the figure, it can be seen intuitively that the fitting effect of the Langmiur isotherm adsorption model is better. As shown in Table 3, under the condition of 20℃, the R 2 The value is 0.990, which is consistent with the R 2 The value is 0.936, which is not much different. This shows that after the material is doped with metal ions Ti, the adsorption process of the adsorbent material is not a simple monolayer adsorption, but a double process of monolayer adsorption and non-uniform surface adsorption. This is also confirmed by the results of the SEM image. At the same time, it is also obtained that the metal ion Ti 3+ After doping, the Ti-MIL-101 material has a better adsorption capacity for uranyl ions than the original MIL-101 (Cr) material. At a temperature of 20°C, the upper limit of the adsorption of uranyl ions by Ti-MIL-101 reached 326.51 mg·g -1 , which is significantly greater than the experimental value of 241.15 mg·L -1This indicates that some experimental conditions did not reach the optimal experimental conditions, and the adsorption capacity of Ti-MIL-101 can be improved. In addition, as the temperature rises, the adsorption capacity of the material on uranyl ions is also increasing, which means that the temperature factor is a positive variable for the adsorption effect of Ti-MIL-101 adsorption material on uranyl ions.
[0100] Table 3 Fitting parameters of Ti-MIL-101 adsorption isotherm model
[0101]
[0102] In three different temperature environments, experimental data on the initial concentration of uranyl ions and the adsorption amount of AO-Ti-MIL-101 materials were obtained, such as Fig.11 The maximum adsorption capacity of AO-Ti-MIL-101 at 20 °C is 385.58 mg g -1 , higher than 241.15mg·g of Ti-MIL-101 material -1 This shows that after AO modification, the adsorption performance of the material will be significantly improved, which is also consistent with the BET specific surface area data.
[0103] The adsorption data of AO-Ti-MIL-101 were linearly simulated using the Langmiur model and the Freundlich model. The simulation results are shown in Fig.12 , Fig.13 As shown in Figure 3, the fitting degree between the Langmiur isotherm adsorption model and the Freundlich isotherm adsorption model is very similar.
[0104] It can be seen from Table 4 that under 20℃ condition, the R 2 The value is 0.967, which is greater than the R of the Freundlich isotherm fitting model. 2 The value is 0.902, but the R 2 The values are quite close, which means that the adsorption process of AO-Ti-MIL-101 adsorbent material is not a simple monolayer adsorption, but a double process of monolayer adsorption and non-uniform surface adsorption. At the same time, it is also obtained that the maximum adsorption capacity of AO-Ti-MIL-101 for uranyl ions at 20 °C is 404.67 mg·g -1 , close to the experimental result of 385.58 mg·L -1 , and its adsorption capacity is higher than that of MIL-101(Cr) and Ti-MIL-101 materials. This shows that the modification of AO can significantly enhance the adsorption capacity of the material for uranyl ions. In addition, with the increase of temperature, the adsorption amount of uranyl ions by the material is also increasing, which means that the temperature factor is a positive variable for the adsorption effect of AO-Ti-MIL-101 adsorption material on uranyl ions.
[0105] Table 4 Fitting parameters of AO-Ti-MIL-101 adsorption isotherm model
[0106]
[0107] 1.4 Stability Analysis
[0108] Depend on Fig.14 As shown in the figure, compared with the material that has not been tested, the peak shape on the XRD graph of the material after the adsorption experiment has not changed significantly, the peak position has not shifted, and the characteristic peak is obvious, which proves that the structure of the material has not changed; Fig.15 (a) and (b) show that the spatial structure of Ti-MIL-101 did not change significantly before and after adsorption. Fig.15 (c) and (d) show that there is no obvious change in the spatial material before and after the adsorption of AO-Ti-MIL-101, which confirms the conclusion obtained from the XRD diagram.
[0109] FTIR of AO-Ti-MIL-101 before and after adsorption of uranium in water Fig.16 As shown. 1539cm -1 The peak shape at 2860~2970cm has basically not changed, indicating that the adsorption of U on the material does not affect the structure of the AO group. -1 The OH or CH peaks nearby disappear and the 754 cm -1 、584cm -1 The peak intensity weakened at , which may be because the adsorption of uranyl ions further reduced the content of crystal water.
[0110] The above shows and describes the basic principles, main features and advantages of the present invention. It should be understood by those skilled in the art that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, which fall within the scope of the present invention to be protected. The scope of protection of the present invention is defined by the attached claims and their equivalents.
Claims
1. An amidoxime-modified and titanium-doped MOFs material, characterized in that: The composition is AO-Ti-MIL-101.
2. A method for preparing amidoxime-modified and titanium-doped MOFs material, characterized in that: include: Step 1: Using terephthalic acid and chromium nitrate nonahydrate as raw materials, MIL-101(Cr) was synthesized by a solvothermal method; Step 2: Using MIL-101(Cr) and butyl titanate as raw materials, shaking and mixing, and then performing a replacement reaction to obtain a Ti-doped MIL-101 material; Step 3: Using Ti-doped MIL-101 material and aminoacetonitrile as raw materials, prepare aminoacetonitrile functionalized Ti-MIL-101 material; prepare hydroxylamine hydrochloride solution, dissolve the aminoacetonitrile functionalized Ti-MIL-101 material in the hydroxylamine hydrochloride solution, and obtain AO-Ti-MIL-101 after centrifugation and drying.
3. The method for preparing an amidoxime-modified and titanium-doped MOFs material according to claim 2, characterized in that: Step 1 includes: Step 1.1: Weigh terephthalic acid and dissolve it in water, stir it with electromagnetic stirring to dissolve, and obtain a white suspension; Step 1.2: Weigh chromium nitrate nonahydrate and dissolve it in ultrapure water, and sequentially treat it with electromagnetic stirring and ultrasonic vibration to obtain a dark green solution; Step 1.3: The two liquids obtained in step 1.1 and step 1.2 are mixed, stirred thoroughly and transferred to a high-pressure reactor, and the high-pressure reactor is placed in a forced air drying oven for reaction to obtain a green suspension containing MIL-101 (Cr). Step 1.4: Place the green suspension in step 1.3 in a centrifuge to obtain a green solid precipitate; Step 1.5: The green solid precipitate is washed with DMF, anhydrous ethanol and ultrapure water for 8 hours in sequence to remove impurities in the pores; and after centrifugation, suction filtration, vacuum drying and grinding, a green powdery MIL-101 (Cr) material is obtained.
4. The method for preparing an amidoxime-modified and titanium-doped MOFs material according to claim 3, characterized in that: Step 2 includes: Step 2.1: Disperse butyl titanate in anhydrous ethanol, then add MIL-101(Cr) and fully dissolve it; Step 2.2: Place the mixed solution of step 2.1 in an oscillator for treatment; Step 2.3: The mixed solution after the shaking treatment is placed in a vacuum drying oven for replacement reaction, and finally separated and dried to obtain the metal ion Ti-doped MIL-101 material.
5. The method for preparing an amidoxime-modified and titanium-doped MOFs material according to claim 4, characterized in that: Step 3 includes: Step 3.1: Disperse the Ti-MIL-101 material in anhydrous toluene, add aminoacetonitrile, condense and reflux under magnetic stirring, and then wash out the aminoacetonitrile functionalized Ti-MIL-101 material, i.e., AA-Ti-MIL-101, with anhydrous ethanol; Step 3.2: dissolving methanol in deionized water, and then dissolving hydroxylamine hydrochloride in the methanol solution; Step 3.3: dissolving the AA-MIL-101 prepared in step 3.1 in the solution prepared in step 3.2, adjusting the pH value of the solution to 7, stirring, and centrifuging; Step 3.3: The sample obtained by centrifugation in step 3.3 is placed in a vacuum drying oven for drying, and finally amidoxime functionalized MIL-101 material, namely AO-Ti-MIL-101, is obtained.
6. The method for preparing an amidoxime-modified and titanium-doped MOFs material according to claim 5, characterized in that: In step 1.3, the high-pressure reactor is placed in a forced air drying oven and reacted at 180° C. for 480 min.
7. The method for preparing an amidoxime-modified and titanium-doped MOFs material according to claim 6, characterized in that: In step 2.1, the mass ratio of butyl titanate to anhydrous ethanol is 1:2; the mass ratio of MIL-101(Cr) to butyl titanate is 1:
2.
8. The method for preparing an amidoxime-modified and titanium-doped MOFs material according to claim 7, characterized in that: In step 3.1, the mass ratio of MIL-101(Cr) to aminoacetonitrile is 1:60; the volume ratio of anhydrous toluene to the mass ratio of MIL-101(Cr) is 60 mL:1 g.
9. The amidoxime-modified and titanium-doped MOFs material according to claim 1, characterized in that: The invention is used for preparing uranium adsorbent.